Training On How to Quickly Memorize The Qur'an Through The Taqriroh Method At TPQ Nurul Amal Lamongrejo Village - Khotimatus Sholikhah; Sokhibun Najah; Ahmad Zakki Jauhari; Fani Herliana (Shof Literacy Community, 2024)
The current generation of memorizers of the Qur'an is increasing. The government has taken part in giving the attention of huffadz, namely by providing scholarship programs at every level of education. The purpose of this service activity is to improve the ability or competence of students in memorizing the Qur'an at TPQ Nurul Amal Lamongrejo Village which includes planning, implementation, and evaluation. The method used is to use a qualitative approach with the type of case study research. The results obtained that the strategy of memorizing the Qur'an through the taqriroh method at TPQ Nurul Amal Lamongrejo has been implemented well. It is hoped that this training can improve the Qur'anic literacy skills of students at TPQ Nurul Amal Lamongrejo, Ngimbang District, Lamongan Regency.